Speech Act (Im)Politeness and Audiovisual Constraints in Translation for Dubbing: Gain, Loss, or Both? - Napoli, Vittorio (Journal of Audiovisual Translation, 2020)
The present article sets out to explore the under-researched relationship between linguistic (im)politeness and audiovisual translation, by taking the speech act of requests as object of analysis in English films and in their dubbed Italian versions. As dubbing constraints often lead translators to depart substantially from the original utterance, the study shows how linguistic changes can result in alterations of the (im)polite load inherent in the requests from original film versions. The study focuses on pragmatic strategies for realizing requests in English film dialogues and shows that dubbing constraints may underlie the adoption of different pragmatic strategies for the requests of target-language dialogues. The (im)politeness shifts that this linguistic modification process entails may make the same character come across as more or less (im)polite in the target-language version and are, for this reason, worth investigating.